Support from teachers and trainers in Vocational education and training: The pathways to career aspirations and further career development - Claudia Hofmann; Barbara E. Stalder; Franziska Tschan; Kurt Häfeli (International Journal for Research in Vocational Education and Training (IJRVET), 2014)
Transition from school to work is a challenging period for young people with learning difficulties. In the dual vocational system of Switzerland, teachers at vocational educational and training (VET)-schools, as well as trainers at VETcompanies, provide~ important support. We were interested in the different pathways from this support to apprentice's career aspirations and further training. Structural equation modelling was used to analyse data from a longitudinal study in four occupational sectors. Results show that VET-teacher support is directly and indirectly related to career aspirations at the end of the apprenticeship, whereas VET-trainer support influences career aspirations only indirectly. Domain specific constructs (ability self-concept at VET-school, skill variety at the VET-company) and self-esteem are important as intermediary variables. Ability self-concept at VET-school had a strong influence on further education three years after the apprenticeship.
Keywords: 330; School-to-work transition; special educational needs; learning difficulties; social support; vocational education and training; longitudinal study